EXPLORING THE EFFECTIVENESS ROLE OF BOARD CHARACTERISTICS ON FIRM PERFORMANCE: A STUDY IN A SAMPLE OF GCC - Mohammed A. Husain (Transpublika Publisher, 2024)
The primary goal of this comparative study is to ascertain the relationship between the performance of firms in Bahrain and Oman and the selected corporate governance procedures. The structured methodology of the study combines a thorough literature review with empirical analysis to accomplish these research goals. A purposeful sample of listed firms in Bahrain and Oman is used to gather financial and governance data, which is then evaluated using regression analysis to test the hypotheses. The results of this study have significant implications for various stakeholders. Regulators can use the findings to create frameworks that support good corporate governance practices, contributing to economic stability and prosperity. Investors can benefit from understanding how specific governance methods impact businesses' financial success, enabling them to make informed investment decisions. Additionally, the report offers valuable guidance for companies operating in Bahrain and Oman on how to enhance corporate governance processes to improve financial results and ensure long-term viability. This comparative study aims to advance knowledge in the fields of corporate governance and company performance research, particularly in the contexts of Bahrain and Oman, by providing insights into the effects of CEO duality, board size, audit committee meetings, and risk management committee meetings on company financial performance.